ANALISIS TINGKAT ARTIFICIAL INTELEGENCE LITERACY PADA MAHASISWA ILMU PERPUSTAKAAN DAN SAINS INFORMASI UNIVERSITAS MUHAMMADIYAH MATARAM - Susilawati, Hirma (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2025)
This study aims to analyze the level of Artificial Intelligence (AI) literacy and the challenges faced by students of the Library and Information Science Study Program at Universitas Muhammadiyah Mataram. AI literacy is a critical competency in the digital era, encompassing conceptual understanding, practical skills, ethical awareness, and reflective attitudes toward intelligent technologies. The research employs a mixed-methods approach with a sequential explanatory design, beginning with quantitative data collection through a Likert-scale questionnaire administered to 88 respondents, followed by in-depth interviews to elaborate on the quantitative findings.The results indicate that the majority of students (98.9%) possess a high level of AI literacy. Students demonstrated strong comprehension of core AI concepts, active usage of AI-based applications in academic activities, and awareness of data security and ethical considerations. The qualitative analysis supported these findings but also revealed several challenges, including limited technical understanding of how AI operates, lack of formal academic guidance, insufficient access to devices and stable internet, and language barriers in AI interfaces.This study concludes that although students exhibit a high degree of AI literacy, there is a need for curricular integration, institutional policy development, and structured pedagogical support to ensure that students can use AI critically, ethically, and responsibly in supporting learning and information management in the context of Society 5.0.